Torque Analysis of 2 KW BLDC (Brushless Direct Current) Motor with Speed Variations in Electric Cars E-Falco - Bambang Darmono; Hadi Pranoto; Zainal Arifin (Institute for Research on Innovation and Industrial System (IRIS), 2021)
The motor releases torque and power to drive an electric car by carrying the load from a start position until it travels at the desired speed. The KMLI E-Falco electric car uses a BLDC type electric motor with a power capacity of 2 kW. To find out the amount of torque of a 2 kW BLDC motor when driving with variations in speed, it can be done by manual calculations using the torque equation and doing a dynotest test. The dynotest results show that the motor torque at the speed: 1 km/h is 1 Nm, 10 km/h is 131 Nm, 13 km/h is 228 Nm, 20 km/h is 225 Nm, 30 km/h is 219 Nm, 40 km / h is 188 Nm, 50 km / hour is 145 Nm, 60 km / h is 113 Nm, and 70 km / h is 85 Nm. From the results of the dynotest, it shows that the peak torque occurs at a speed of 13 km / h at 228 Nm. Racing software installed in the controller can increase the motor torque by four times at a speed variation of 13-70 km/h based on the results of the dynotest above. Keywords: motor, BLDC, torque, speed, acceleration.